2015
DOI: 10.1002/jobm.201500444
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and biochemical characterization of recombinant superoxide dismutase from Antarctic psychrophilic bacterium Pseudoalteromonas sp. ANT506

Abstract: In this study, a superoxide dismutase gene (PsSOD) from Pseudoalteromonas sp. ANT506 was cloned and over expressed in Escherichia coli. The PsSOD has an open reading frame of 582 bp with a putative product of 193 amino acid residue and an estimated molecular size of 21.4 kDa. His-tagged PsSOD was subsequently purified 12.6-fold by Ni-affinity chromatography and the yield of 22.9%. The characterization of the purified rPsSOD exhibited maximum activity at 30 °C and pH 8.0. The enzyme exhibited 13.9% activity at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…), which suggested that RmFeSOD was a dimeric protein composed of two 23.5 kDa subunits. The dimeric organization of RmFeSOD, being similar to most of typical Fe‐SODs , could increase enzymatic flexibility to adapt the extreme conditions .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…), which suggested that RmFeSOD was a dimeric protein composed of two 23.5 kDa subunits. The dimeric organization of RmFeSOD, being similar to most of typical Fe‐SODs , could increase enzymatic flexibility to adapt the extreme conditions .…”
Section: Resultsmentioning
confidence: 99%
“…According to reports, Pseudoalteromonas sp. ANT506 Fe‐SOD had conservative WEHAYY sequence and conservative amino acid binding site of iron: His 18 , His 74 , His 167 , and Asp 162 . Sonneratia alba Fe‐SOD had conserved amino acids of WEHAYY and conserved Fe‐binding sites: His 27 , His 80 , Asp 164 , and His 168 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations